Bayesian nonparametrics for stochastic epidemic models - Kypraios, Theodore; O'Neill, Philip D. (Institute of Mathematical Statistics, 2018)
The vast majority of models for the spread of communicable diseases are parametric in nature and involve underlying assumptions about how the disease spreads through a population. In this article we consider the use of Bayesian nonparametric approaches to analysing data from disease outbreaks. Specifically we focus on methods for estimating the infection process in simple models under the assumption that this process has an explicit time-dependence.